Role of Human Resources in the Mergers and Acquisitions Processes - Anna Szewczyk (Contemporary Economics)
The human resources are one of the most important topics when you talk about the value and importance of a company itself. The article tries to show the different aspects where the human resource affects a merger in the different states of a merger process, especially to the pre-merger-phase, and to which problems it can lead when you not pay attention to it. Finally the question, which is indeed the most important aim concerning mergers namely: how and in which degree the human resource effects the goodwill, is tried to answer.